Synthesis and evaluation of multi-functional NO-donor/insulin-secretagogue derivatives for the treatment of type II diabetes and its cardiovascular complications. Issue 3 (1st February 2015) - Digiacomo, Maria; Martelli, Alma; Testai, Lara; Lapucci, Annalina; Breschi, Maria C.; Calderone, Vincenzo; Rapposelli, Simona
Graphical abstract: Abstract: Although there is a significant effort in the discovery of effective therapies to contrast both the pathological endocrine and metabolic aspects of diabetes and the endothelial dysfunction associated with this disease, no hypoglycemic drug has been proven to defeat the cardiovascular complications associated with type II diabetes. The aim of this research was to design new compounds exhibiting a double profile of hypoglycemic agents/NO-donors. The synthesis of molecules obtained by the conjunction of NO-donor moieties with two oral insulin-secretagogue drugs (repaglinide and nateglinide) was reported. NO-mediated vasorelaxing effects of the synthesized compounds were evaluated by functional tests on isolated endothelium-denuded rat aortic rings . The most potent molecule (4 ) was tested to evaluate the hypoglycemic and the anti-ischemic cardioprotective activities. This study indicates that4 should represent a new insulin-secretagogue/NO-donor prodrug with an enhanced cardiovascular activity, which may contrast the pathological aspects of diabetes and endowed of cardioprotective activity.